TREND AJAKAN NIKAH MUDA DI MEDIA SOSIAL: (ANALISIS WACANA PERSUASIF DAN IMPLEMENTASINYA) - Ilma Maula, Afida (USRATUNA: Jurnal Hukum Keluarga Islam, 2023)
Early marriage is a phenomenon that occurs among society. In fact, in some places, early marriage is considered a culture within a group of people. Unfortunately, early marriage also contributes to divorce cases. The spread of discourse on early marriage is currently being done through social media, making it spread quickly. However, it is also necessary to examine how the method or content presented by early marriage accounts and how society can be influenced by persuasive discourse on these accounts. This paper uses qualitative research with a netographic field research approach. In addition, the analysis in this study uses Van Dijk's critical persuasive discourse theory. This study takes data through related articles and interviews. This study specifically examines three accounts that have persuasive discourse on early marriage, namely @nikahasik, @indonesiatanpapacaran, and @gerkannikahmuda. The results of the research in this paper are that there are 3 dimensions for analyzing persuasive discourse, namely the text dimension that the content has substance to immediately get married with religious wrapping, social cognition that the content stems from community complaints and observations of content creators, and social context that there are pros and cons in it. Based on interviews with people who follow persuasive discourse accounts on early marriage, the substance of the content does not provide much or even no influence to immediately get married.